Is white matter affected in adolescents with anorexia nervosa? A study using magnetization transfer imaging - Akgül, Sinem; Öz, Ayşegül; Karlı-Oğuz, Kader; Kanbur, Nuray; Derman, Orhan (The Turkish Journal of Pediatrics, 2016)
The aim of the study was to assess potential changes in structural integrity of the brain in adolescent patients with Anorexia Nervosa (AN) using the magnetization transfer imaging technique and re-evaluating after nutritional rehabilitation was accomplished. Magnetization transfer ratio (MTR) was used for the detection and quantification of histological changes to the white matter of 9 adolescents diagnosed with AN at diagnosis and after weight gain. Using the MTR technique 6 regions were measured: the pons, left cerebellar hemisphere, amygdala, thalamus, corona radiata and white matter adjacent to the left dorsolateral prefrontal cortex. Scans from the patients with AN were also compared with scans from an age-matched subset of 9 healthy controls. Compared with control subjects, the MTR of participants with AN was no different either at the early stages of diagnosis (p=0.62) or after weight recovery (p=0.81). Similarly, comparison of MTR between patients with AN at diagnoses compared with MTR after weight recovery yielded no statistically significant difference (P=0.33). We conclude that MTR was not able to detect any neuropathological alterations in adolescent patients with AN at either diagnosis or after nutritional recovery and the achievement of weight gain.